Analysis of Hybrid Ejector Absorption Cooling System. (2nd September 2019) - Sioud, Doniazed; Bellagi, Ahmed
Abstract : In this paper, a hybrid ejector single-effect lithium-bromide water cycle is theoretically investigated. The system is a conventional single-effect cycle activated by an external steam-ejector loop. A mathematical model of the whole system is developed. Simulations are carried out to study the effect of the major parameters of the hybrid cycle on its performances and in comparison with the conventional cycle. The ejector performance is also investigated. Results show that the entrainment ratio rises with steam pressure and condenser temperature, while it decreases with increasing generator temperature. The effect of the evaporator temperature on ejector performance is negligible. It is shown also that the hybrid cycle exhibits better performances than the corresponding basic cycle. However, the performance improvement is limited to a specific range of the operating parameters. Outside this range, the hybrid system behaves similar to a conventional cycle. Inside this range, theC O P increases, reaches a maximum, and then decreases and rejoins the behavior of the basic cycle. The maximumC O P, which can be as large as that of a conventional double-effect cycle, about 1, is obtained at lower temperatures than in the case of single-effect cycles.